AMERICAN POLONIA’S RESOURCES OF IFLUENCE AND US FOREIGN POLICY - I. D. Loshkariov (Vestnik MGIMO-Universiteta)
The article analyzes resources of political influence on the foreign policy of the country of residence that Polish diaspora in the United States possesses. This analysis is useful for two reasons. Firstly, it will expand the focus of research in the study of pressure groups and their influence on the American foreign policy. Secondly, the Polish diaspora in the United States is rarely the object of research in migrant and ethnic lobbying, despite its the significant share of the country’s population. Analysis of the given resources that the Polish diaspora (American Polonia) has leads to the following. Firstly, the foreign policy agenda of the Polish diaspora in the United States faces no strong opponents. This fact means the diaspora has sufficiently developed structural resource. In addition, the Polish diaspora possesses an organizational resource: its institutions are in close cooperation and are coordinated by the Polish American Congress. Secondly, the Polish diaspora in the US is a significant group of the population, especially in the states of Wisconsin, Michigan, Connecticut, New York and Illinois. However, its electoral and financial capacities are not used to the fullest extent. Finally, there are certain difficulties with the discursive political resource of Polish diaspora. The social and political perception provides of Polonia in the USA two opposing narratives. The first one stresses that it is important for the Americans of Polish descent to share such values as democracy, defending his position, including by military means. The second narrative is a reproduction of widespread stereotypes about Poles, including in the popular culture. Thus, institutions of the American Polonia face several tasks. The most important tasks are the search for new ways of political mobilization of the diaspora and the formation of a balanced image of Polish Americans in the social and political perception in the United States.